Intra- and inter-examiner reproducibility of manual probing depth - Roberto Andrade; Manuel Espinoza; Elena Maria Gómez; José Rolando Espinoza; Elizabeth Cruz (Sociedade Brasileira de Pesquisa Odontológica, 2012)
The periodontal probe remains the best clinical diagnostic tool for the collection of information regarding the health status and the attachment level of periodontal tissues. The aim of this study was to evaluate intra- and inter-examiner reproducibility of probing depth (PD) measurements made with a manual probe. With the approval of an Ethics Committee, 20 individuals without periodontal disease were selected if they presented at least 6 teeth per quadrant. Using a Williams periodontal probe, three calibrated thesis-level students (k > 0.6) assessed PD at 6 sites per tooth, from the gingival margin to the bottom of the periodontal sulcus (rounded to the next 0.5 mm). Initial and repeated measurements were performed by the same three examiners. The intra-examiner agreement (± 1 mm > 90%) was 99.85%, 100%, and 100% for the three examiners, respectively. When the variables vestibular/lingual surfaces, mesial/distal surfaces, or superior/inferior jaws were evaluated, no significant differences in reproducibility were detected at the inter-examiner level (p < 0.05). At this level, the only significant differences observed were in the three examiners' measurements of the anterior and posterior sites. While high intra-examiner reproducibility was detected, inter-examiner level proved to be low. We can conclude that measurement of PD with a manual periodontal probe produced high reproducibility in healthy individuals. The operator's position can affect the reproducibility of repeated measures of PD. Calibration and operator training, rather than operator experience, were fundamental for reproducibility. Other factors, such as individual technique and probing depth force, can affect inter-examiner reproducibility.